The Effects of Different Agitation Techniques of Canal Irrigant on Tubular Penetration of a Bioceramic Sealer - Zand, Vahid; Salem Milani, Amin; Yavari, Hamid Reza; Majidi, Ali reza (Iranian Endodontic Journal, 2019)
Introduction: This study aimed to compare the effects of different agitation techniques of sodium hypochlorite (NaOCL) as the final irrigation with XP-Finisher file, passive ultrasonic irrigation (PUI), Er:YAG laser and irrigation with conventional syringes, on penetration of Sure Seal Root bioceramic sealer into dentinal tubules. Methods and Materials: Forty freshly extracted single-rooted human teeth were included in the present in vitro study. All the teeth were prepared up to #40 (4%) with Bio Race rotary file system, using crown-down technique. After chemomechanical preparation, the teeth were randomly assigned to 4 groups based on the agitation protocol: conventional needle irrigation (CNI) with a 30-G needle in a syringe, PUI, Er:YAG laser and XP-Finisher file, Subsequent to the agitation procedure, the root canals were obturated with tapered bioceramic-covered gutta-percha point and, bioceramic sealer, using the single-cone technique. The maximum penetration of the sealer into the dentinal tubules was determined in the coronal, middle and apical thirds using the scanning electron microscope (SEM) technique. After confirmation of the normal distribution of data with Shapiro-Wilk test, Data were analyzed using the one-way ANOVA and Tukey tests. Results: The mean penetration depth of the bioceramic sealer into the dentinal tubules in the PUI group was greater than that of other groups; however, the difference between the two PUI and Er:YAG laser groups in the apical third was not significant (P=0.078). Er:YAG laser, PUI and XP-Finisher file agitation techniques resulted in significantly greater penetration of the bioceramic sealer into the dentinal tubules compared to the CNI (P<0.001). The XP-Finisher file technique in the apical (P=0.752) and middle thirds (P=0.339) and the Er:YAG laser technique in the apical thirds (P=0.086) were not significantly different from the conventional irrigation technique. Conclusion: The PUI technique resulted in significantly deeper penetration of the Bioceramic sealer into the dentinal tubules compared to the three other techniques. Keywords: Endodontics; Lasers; Root Canal Preparation; Ultrasonic; XP Endo Finisher